Amphiregulin-producing γδ T cells are vital for safeguarding oral barrier immune homeostasis - Krishnan, Siddharth; Prise, Ian E.; Wemyss, Kelly; Schenck, Louis P.; Bridgeman, Hayley M.; Mcclure, Flora A.; Zangerle-Murray, Tamsin; O'Boyle, Conor; Barbera, Thomas A.; Mahmood, Faiza; Bowdish, Dawn M. E.; Zaiss, Dietmar M. W.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
γδ T cells are enriched at barrier sites such as the gut, skin, and lung, where their roles in maintaining barrier integrity are well established. However, how these cells contribute to homeostasis at the gingiva, a key oral barrier and site of the common chronic inflammatory disease periodontitis, has not been explored. Here we demonstrate that the gingiva is policed by γδ T cells with a T cell receptor (TCR) repertoire that diversifies during development. Gingival γδ T cells accumulated rapidly after birth in response to barrier damage, and strikingly, their absence resulted in enhanced pathology inmurine models of the oral inflammatory disease periodontitis. Alterations in bacterial communities could not account for the increased disease severity seen in γδ T cell-deficient mice. Instead, gingival γδ T cells produced the wound healing associated cytokine amphiregulin, administration of which rescued the elevated oral pathology of tcrδ-/- mice. Collectively, our results identify γδ T cells as critical constituents of the immuno-surveillance network that safeguard gingival tissue homeostasis.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Amphiregulin; Mucosal immunology; γδ T cells